Some Aspects Of The Biology Of Hampala Macrolepidota (Van Hasselt) With Reference To Its Food, Feeding, Habits And Reproduction From Zoo Negara Lake, Kuala Lumpur, Malaysia - Zainal abidin, Aizam (1984)
A study on some aspects of the biology of Hampafa macholepidota ( Van Hasselt ) with emphasis on its food , feeding habits and reproduction was carried out at Zoo Negara Lake , Kuala Lumpur ,Malaysia The length-weight relationships of male and female adult fishes are : - Log L = 3.114 Log W - 11.9034 and Log L =3.461 Log W - 13.8770, respectively. The length-weight relationship of the combined male and female fishes is : - Log L =3.256 Log W-12.692 The form of the mout h and its action , dentition,gill rakers, form of the alimentary canal and stomach are described and the significance of these features are discussed.